2015
DOI: 10.1080/01445340.2015.1065459
|View full text |Cite
|
Sign up to set email alerts
|

Programming Primes (1968–1976): A Paradigmatic Program and Its Incarnations in the Age of Structured Programming

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It also showed that digital computing could not only tackle the practical problems in ballistics or other problems related to differential equations and continouous mathematics that analogue machines could handle already, but new classes of problems altogether. Lastly, the little number-theoretical programs contained enough logical complexity, using all or most elementary instructions, so that they were good 13 This posterity of the EDSAC primes program is framed in a broader historical context in [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also showed that digital computing could not only tackle the practical problems in ballistics or other problems related to differential equations and continouous mathematics that analogue machines could handle already, but new classes of problems altogether. Lastly, the little number-theoretical programs contained enough logical complexity, using all or most elementary instructions, so that they were good 13 This posterity of the EDSAC primes program is framed in a broader historical context in [8].…”
Section: Discussionmentioning
confidence: 99%
“…Because the ENIAC card reader was slow (compared to its computation time, viz. 0.48 s versus .2 ms) and memory was at a premium, 8 Lehmer decided not to input the list of prime numbers via punched cards, but to let the ENIAC calculate its own primes, using Eratosthenes' sieve. To start with, Lehmer only sifted through the odd numbers, stepping +2 for each new number P .…”
Section: Dh Lehmer's Prime Sieve On the Eniacmentioning
confidence: 99%
See 1 more Smart Citation